Simulation Of Active Force Control Using Intelligent Methods To Reduce Vibration Of The Suspended Handle - Wong, Jen Nyap (Universiti Sains Malaysia, 2018)
This study focuses on the vibration attenuation of the suspended handle generated from the power tools using different type of Active Force Control (AFC) tuning strategies. The suspended handle is modelled as a single-degree-of-freedom (SDOF) system with the parameters of mass, spring and damping taken from the previous research. The model of internal disturbance is also taken from the previous research while two new models of external disturbances are introduced during the simulation process to evaluate the robustness of the system. Four types of control schemes are investigated and compared in suppressing the vibration of the handle, which are Proportional-Integral-Derivative (PID) controller, PID-AFC-Crude Approximation (CA), PID-AFC-Fuzzy Logic (FL) and PID-AFC-Iterative Learning Method (ILM) control schemes. From the simulation, AFCCA scheme generates the best performance when the estimated mass (EM) is 0.04 kg. While for the AFCFL scheme, the best response is generated with the membership function of trapezoidal shape with EM of 0.040295 kg. Furthermore, the AFCILM scheme shows the best response with EM of 0.040000261 kg and both learning parameters A and B at value of 0.6. By comparing the results among the systems, AFCILM scheme shows the best overall performance for the zero input signal while AFCCA gives the best response for the step input signal.